Treatment of toponyms with the application of geotechnologies. Study case: Ingeniero White, Argentina (Huellas, 2023)
Toponymy is a discipline that studies the proper names of places. For Geography, toponyms are important because they provide information about a specific space. At present, georeferenced territorial information in digital format is of growing relevance, so the present work aims to apply geotechnologies to the treatment of toponyms at scale 1:25 000 of the sector of Ingeniero White, covered by the chart of Bahía Blanca 3963-17-1, prepared by the National Geographic Institute (I.G.N.). For this purpose, a quali-quantitative methodological approach was chosen, which included the survey, selection and analysis of information, the creation of an alphanumeric database and the use of geotechnologies for the spatial treatment of toponyms and their information, by means of a Geographic Information System (G.I.S.). The result was the creation of a dynamic consultation system through the use of pop-up windows that allow interaction with the geolocalized toponyms. It can be concluded that the creation of a database of toponyms and its visualization in a G.I.S. allows the presentation of information and its consultation in a dynamic way to analyze information about changes in the names of places, in this case of Ingeniero White.
Keywords: Toponyms; Geotechnologies; G.I.S.; Ingeniero White; geography; pop-up windows